2011
DOI: 10.1182/blood-2010-09-307983
|View full text |Cite
|
Sign up to set email alerts
|

B-cell depletion reactivates B lymphopoiesis in the BM and rejuvenates the B lineage in aging

Abstract: IntroductionThe aging of the immune system involves many physiologic changes that are collectively referred to as immune senescence. These changes affect both the innate and the adaptive immune system, often resulting in an immunodeficient state that is currently incompletely understood. The most important immunologic manifestations in aging include poor responsiveness to new or evolving pathogens and reduced efficacy of vaccination. 1,2 Primary causes of this immune incompetence are the decline in production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
77
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 50 publications
10
77
1
3
Order By: Relevance
“…Recently, we showed that depletion of peripheral B cells in old mice reactivates B lymphopoiesis in the BM, thereby supporting the argument that reduction of B lymphopoiesis with aging is an adaptive homeostatic response to the accumulation of long-lived memory B cells in the periphery (19,20). The results shown here further support this argument by showing that in mutated mice, where long-lived B cells do not accumulate, B lymphopoiesis does not significantly change with age, and a high output of B cells from the BM is maintained in aging.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Recently, we showed that depletion of peripheral B cells in old mice reactivates B lymphopoiesis in the BM, thereby supporting the argument that reduction of B lymphopoiesis with aging is an adaptive homeostatic response to the accumulation of long-lived memory B cells in the periphery (19,20). The results shown here further support this argument by showing that in mutated mice, where long-lived B cells do not accumulate, B lymphopoiesis does not significantly change with age, and a high output of B cells from the BM is maintained in aging.…”
Section: Discussionsupporting
confidence: 63%
“…It is important to note that the use of the 3-83Tg model has some disadvantages for repertoire analysis due to the nature of selection and expansion of Tg and non-Tg variant B cells. Thus, although this approach is well accepted (2,10,20), it would be important to confirm these results in a non-Tg system in future studies.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations